PENGARUH TINGKAT SUKU BUNGA, TINGKAT RISIKO KREDIT, RISIKO LIKUIDITAS, RISIKO OPERASIONAL TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PADA TAHUN 2020- 2022 - Ningtias, Erika Framita; Lilia, Wirda; Gustarina, Elina R. (Journal Accounting International Mount Hope, 2025)
The purpose of this study is to conduct an analysis of interest rates, credit risk levels, liquidity risk, operational risk on stock returns. This research approach is based on a quantitative approach. The population in this study is pharmaceutical sub-sector companies listed on the IDX. The number of samples is 11 pharmaceutical companies with 33 observations. The data analysis technique uses multiple linear regression analysis. The conclusion in the study is that interest rates, credit risk and operational risk do not have a partial effect on stock returns while liquidity risk has a partial positive effect on stock returns. While simultaneously interest rates, credit risk levels, liquidity risk, operational risk have an effect on stock returns of manufacturing companies listed on the IDX in 2020-2022.